(untitled) (Confluenţe Bibliologice, 2021)
In the last issue of ONT magazine, the author makes a brief presentation of what the National Tourism Office meant in the interwar period. It was initiated in 1924 and in 1936, ONT acquires an organizational character, with a well-defined status, within the Ministry of Interior. ONT has taken the initiative to build tourist hotels and other buildings useful for tourism in balneary and tourist centers, meant to attract more visitors. We can also find the article that refers to the Romanian Popular Art, beautifully illustrated with 39 images, from which certain passages are selected: the costume, the carpets, the ceramics. Romanian Popular Music could not be missing from this theme: the lullaby, the carol, sorcova, doina, the wedding song, the ballads. This is how the soul life of the Romanian is depicted through songs.